2022
DOI: 10.1111/tid.13821
|View full text |Cite
|
Sign up to set email alerts
|

Association between gut colonization of vancomycin‐resistant enterococci and liver transplant outcomes

Abstract: Background: Vancomycin-resistant enterococci (VRE) colonization is common in liver transplant recipients and has been associated with worse posttransplant outcomes. Methods:We conducted a retrospective cohort study at the University of Alberta Hospital including patients who underwent a liver transplant between September 2014 and December 2017.Results: Of 343 patients, 68 (19.8%) had pretransplant VRE colonization and 27 (27/275, 9.8%) acquired VRE posttransplant, 67% were males and the median age was 56.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…27 Additionally, a recent study failed to identify differences between VRE-colonized and non-colonized patients regarding post-LT survival. 20,28 An interesting finding in our cohort was the high post-LT mortality rate among patients who had ESBL-producing Enterobacterales infection before LT (51%), which was higher than other pre-LT MDRO infections (39%) and higher than the mortality of patients with pre-…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…27 Additionally, a recent study failed to identify differences between VRE-colonized and non-colonized patients regarding post-LT survival. 20,28 An interesting finding in our cohort was the high post-LT mortality rate among patients who had ESBL-producing Enterobacterales infection before LT (51%), which was higher than other pre-LT MDRO infections (39%) and higher than the mortality of patients with pre-…”
Section: Discussionmentioning
confidence: 76%
“…Regarding VRE colonization, Russell et al reported that VRE colonization increased the risk of death in LT recipients and candidates by more than two‐fold, this was a cross‐section study in ICU and there is no information about the follow up of LT candidates after transplantation 27 . Additionally, a recent study failed to identify differences between VRE‐colonized and non‐colonized patients regarding post‐LT survival 20,28 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical impact of these infections is compounded by rising rates of antibiotic resistance, with vancomycin resistant Enterococcus faecium (VRE) and multiple drug resistant Enterobacterales making outsized contributions to morbidity and mortality. (12,13) Enterococcus and Enterobacterales species are normal inhabitants of the human gut microbiota. (14,15) In healthy individuals, these facultative anaerobes compose a small fraction of the microbiota but are capable of markedly expanding following loss of microbiota diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical impact of these infections is compounded by rising rates of antibiotic resistance, with vancomycin resistant Enterococcus faecium (VRE) and multiple drug resistant Enterobacterales making outsized contributions to morbidity and mortality. (12, 13)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation